Breathing-synchronised electrical stimulation of the abdominal muscles in patients with acute tetraplegia: A prospective proof-of-concept study. (1st November 2016) - Liebscher, Thomas; Schauer, Thomas; Stephan, Ralph; Prilipp, Erik; Niedeggen, Andreas; Ekkernkamp, Axel; Seidl, Rainer O.
Abstract : Objective : To examine whether, by enhancing breathing depth and expectoration, early use of breathing-synchronised electrical stimulation of the abdominal muscles (abdominal functional electrical stimulation, AFES) is able to reduce pulmonary complications during the acute phase of tetraplegia. Design : Prospective proof-of-concept study. Setting : Spinal cord unit at a level 1 trauma center. Method : Following cardiovascular stabilisation, in addition to standard treatments, patients with acute traumatic tetraplegia (ASIA Impairment Scale A or B) underwent breathing-synchronised electrical stimulation of the abdominal muscles to aid expiration and expectoration. The treatment was delivered in 30-minute sessions, twice a day for 90 days. The target was for nine of 15 patients to remain free of pneumonia meeting Centers for Disease Control and Prevention (CDC) diagnostic criteria. Results : Eleven patients were recruited to the study between October 2011 and November 2012. Two patients left the study before completion. None of the patients contracted pneumonia during the study period. No complications from electrical stimulation were observed. AFES led to a statistically significant increase in peak inspiratory and expiratory flows and a non-statistically significant increase in tidal volume and inspiratory and expiratory flow. When surveyed, 6 out of 9 patients (67%) reported that the stimulation procedure led to a significant improvement in breathing and coughing. Conclusion : AFES appears to be able to improve breathing and expectoration and prevent pneumonia in the acute phase of tetraplegia (up to 90 days post-trauma). This result is being validated in a prospective multicentre comparative study.